Sharing Private Space with Strangers: The Phenomenon of Couchsurfing App User - Gita Juniarti (Ikatan Sarjana Komunikasi Indonesia, 2021)
Couchsurfing is an application that connects persons who need lodging, with individuals who offer their house as a free place to stay. Persons who need lodging are called surfers and individuals who provide their house are called hosts. When hosts and surfers are just getting acquainted through the Couchsurfing app, they hold some uncertainty with each other. This study describes the experiences of both parties in their efforts to reduce uncertainty and build close relationships, even though they only met through digital applications and never Â face to face. This study uses a phenomenological approach with data search techniques in the form of in-depth interviews, direct observation, and data observation through the Couchsurfing application. The number of interviewees was 14Â from various cities in Indonesia. To reduce uncertainty and build close relationships, hosts and surfers go through five stages; first, understanding and believing technology; second, pre-conversation; third, online conversation-1; fourth, face-to-face conversation; and fifth, online conversation-2. The description of these stages is summarized in the findings of this study. This finding also proves that the presence of technology may modify the previously known theories of interpersonal communication. Interpersonal communication not only takes place between two people directly but also involves technology as an intermediary.